Penerapan Aplikasi APTAQU (Aplikasi Tafsir Al-Quran Inklusif) Bagi Santri Penyandang Disabilitas Di Pesantren Tunarungu ABATA Temanggung - Ahmad Rifai; Rian Adnan Fauzi; Mohammad Ulyan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The aim of this research is to develop and implement an application called APTAQU, designed to assist students with disabilities, especially those with hearing impairments, at Pesantren Tunarungu ABATA Temanggung in learning the interpretation of the Qur'an (tafsir). This application is developed to address the specific needs of hearing-impaired students, allowing them to access Qur'anic interpretation learning independently and effectively. The research employs a qualitative method, involving students and pesantren mentors actively in each stage, including planning, training, evaluation, and refinement of the application, to ensure that it meets the needs and abilities of the users. The application development process involves direct input from students and mentors, ensuring that the resulting application is truly relevant to their needs. During the development and implementation phases, students were trained to optimize the use of the application. The results of this community service show that the APTAQU application can improve accessibility for hearing-impaired students in understanding the interpretation of the Qur'an, an area that had previously been a major barrier in their learning. Interactive features such as sign language, audio-visual content, screen readers, and voice instructions have proven to help overcome communication barriers present in conventional media that were not inclusive. Moreover, the use of this application has also increased the involvement of students in religious education, particularly in understanding the Qur'anic interpretation. They are now more actively engaged in the learning process and can better comprehend the tafsir material. However, the application still requires further development to become more inclusive and user-friendly for all students, both with and without disabilities. This research contributes significantly to creating a more inclusive and accessible education for people with disabilities, especially in religious education, and serves as a starting point for addressing educational access disparities for them.